The Effect of Innovation, Logistic Performance, and Human Capital on Export Diversification of Manufacturing Industry - Madonna, Melia; Handoyo, Rossanto Dwi (KINERJA, 2023)
This study aimed to analyze the effect of innovation, logistics performance, and human capital on export diversification of the manufacturing industry based on technology intensity in Indonesia. This study uses the method of moments approach with estimation using the Generalized Method of Moments (GMM). The research was conducted using dynamic data panels belonging to Indonesia and 30 main export destination countries as research objects. The results show the average Global Innovation Index (GII) of Indonesia and export countries, the average Logistics Performance Index (LPI) of Indonesia and export destination countries, the labor force with intermediate education, labor force with basic education. Indonesia's GDP has a positive and significant effect on the diversification of manufacturing industry commodity exports in Indonesia across all technological intensities. Still, the importers' GDP and exchange rates positively influence the spread of diversification exports of manufactured industrial commodities in Indonesia, but some models show no significant relationship.